(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
In this article, the training of qualified medical personnel in the field of health care in Andizhan, Ferghana and Namangan regions of the Ferghana Valley, the work carried out in universities and secondary medical educational institutions in this direction, the activities of doctors and medical staff are studied with the help of scientific literature and archival data.